Sources of financing for real estate in Singapore - KOH, Francis (Institutional Knowledge at Singapore Management University, 2019)
Real Estate Investments and Financing may be depicted by the four quadrants model: public equity, private equity, public debt and private debt. This paper discusses the various methods of financing available to real estate companies in Singapore. We showed that the availability of financing for real estate is affected by supply and demand of capital and underlying market conditions. Thus, it is imperative for real estate companies to use a variety of sources to finance their projects. We also provide a discussion of two large property companies in Singapore to illustrate the use of debt and equity for financing real estate investments. This paper contributes to the literature on the four quadrants model in real estate investments and financing.